Multiple drug resistance activity of Clove extract by extraction solvents - Arpha, Nur E; Fariha, Asfika Rahman (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.